Competitive Advantage and Competitive Strategy in Nina Donut Business - Arya Geovany; Ahmad Ikhsan Ramadhan; Ahmad Vajri Rahman (CAKRAWALA : Management Science Journal, 2026)
Competitive advantage plays a crucial role in determining business sustainability, particularly for micro, small, and medium enterprises in the culinary sector. This study aims to analyze the competitive environment, internal strengths and weaknesses, and competitive strategies implemented by Nina Donat to achieve sustainable competitive advantage. This research uses a qualitative descriptive approach through direct observation and literature review. The findings show that product quality consistency, affordable pricing, and close customer relationships are key strengths of Nina Donat. However, limited promotion and production capacity remain challenges. The competitive strategies applied include product differentiation, competitive pricing, service orientation, and simple promotional activities. These strategies contribute to strengthening Nina Donat’s position in the local market. The study confirms that integrated management of product quality, pricing, service, innovation, and consistency is essential to achieve long-term competitive advantage.